Targeting the rheumatoid arthritis synovial fibroblast via cyclin dependent kinase inhibition: An early phase trial. Issue 26 (26th June 2020) - Siebert, Stefan; Pratt, Arthur G.; Stocken, Deborah D.; Morton, Miranda; Cranston, Amy; Cole, Michael; Frame, Sheelagh; Buckley, Christopher D.; Ng, Wan-Fai; Filer, Andrew; McInnes, Iain B.; Isaacs, John D.
Abstract: Introduction: Targeted biologic therapies demonstrate similar efficacies in rheumatoid arthritis despite distinct mechanisms of action. They also exhibit a ceiling effect, with 10% to 20% of patients achieving remission in clinical trials. None of these therapies target synovial fibroblasts, which drive and maintain synovitis. Seliciclib (R-roscovitine) is an orally available cyclin-dependent kinase inhibitor that suppresses fibroblast proliferation, and is efficacious in preclinical arthritis models. We aim to determine the toxicity and preliminary efficacy of seliciclib in combination with biologic therapies, to inform its potential as an adjunctive therapy in rheumatoid arthritis. Methods and analysis: TRAFIC is a non-commercial, multi-center, rolling phase Ib/IIa trial investigating the safety, tolerability, and efficacy of seliciclib in patients with moderate to severe rheumatoid arthritis receiving biologic therapies. All participants receive seliciclib with no control arm. The primary objective of part 1 (phase Ib) is to determine the maximum tolerated dose and safety of seliciclib over 4 weeks of dosing. Part 1 uses a restricted 1-stage Bayesian continual reassessment method based on a target dose-limiting toxicity probability of 35%. Part 2 (phase IIa) assesses the potential efficacy of seliciclib, and is designed as a single arm, single stage early phase trial based on a Fleming-A'Hern design using the maximum tolerated dose recommended from part 1. The primary response outcome after 12 weeks of therapy is a composite of clinical, histological and magnetic resonance imaging scores. Secondary outcomes include adverse events, pharmacodynamic and pharmacokinetic parameters, autoantibodies, and fatigue. Ethics and dissemination: The study has been reviewed and approved by the North East - Tyne & Wear South Research Ethics Committee (reference 14/NE/1075) and the Medicines and Healthcare Products Regulatory Agency (MHRA), United Kingdom. Results will be disseminated through publication in relevant peer-reviewed journals and presentation at national and international conferences. Trials Registration: ISRCTN, ISRCTN36667085. Registered on September 26, 2014; http://www.isrctn.com/ISRCTN36667085 Current protocol version : Protocol version 11.0 (March 21, 2019)